Upaya Pendampingan Pastoral dengan Tehnik Client Center kepada Pemuda “Mr. X” Penyandang Disabilitas yang Tidak Dapat Menerima Dirinya (Jurnal Pendidikan Agama dan Teologi, 2024)
Self-acceptance is an important process for people with disabilities to achieve a better quality of life and optimal mental health. The limitations experienced by people with disabilities have an influence on their self-acceptance. The limitations they experience make people with disabilities feel stressed, have low self-esteem and feel lonely. Support from family, friends and community is the main factor that helps people with disabilities. The aim of this research is that this young man can accept himself as a person with a physical disability. The method used in this research is the case study method, where this method is an in-depth exploration of a bound system based on extensive data collection. Based on this research, people with physical disabilities can be responsible for themselves and their future and must be able to accept the disabilities they experience.